2003
DOI: 10.1007/s00464-002-9258-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different intraabdominal pressures on lipid peroxidation and protein oxidation status during laparoscopic cholecystectomy

Abstract: The results suggest that both 15 and 10 mmHg of LAP could lead to an increased oxidative stress response during LC, but no difference was found between the groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 17 publications
1
52
1
4
Order By: Relevance
“…In their study on rats, Yilmaz et al [42] did not demonstrate any statistical significance in oxidative stress parameters at both low and high intraabdominal pressures. Polat et al [43] confirmed these results in their study with human subjects. A recent study conducted by Biler et al [44] clearly demonstrated that the ischemic preconditioning method should be used to reduce IRIs, rather than other low-pressure models.…”
Section: Iri Secondary To Laparoscopic/robotic Pneumoperitoneummentioning
confidence: 53%
“…In their study on rats, Yilmaz et al [42] did not demonstrate any statistical significance in oxidative stress parameters at both low and high intraabdominal pressures. Polat et al [43] confirmed these results in their study with human subjects. A recent study conducted by Biler et al [44] clearly demonstrated that the ischemic preconditioning method should be used to reduce IRIs, rather than other low-pressure models.…”
Section: Iri Secondary To Laparoscopic/robotic Pneumoperitoneummentioning
confidence: 53%
“…Their study revealed higher transaminase values for the 14 mm Hg group, while the gasless group and 10 mm Hg group displayed almost the same values. Yılmaz et al [25] reported statistically different values of oxidative stress responses for 10 mm Hg and 15 mm Hg groups in a rat model; and Polat et al [13] validated these results in their study with human subjects. Moreover, Guven and et al [27] reported that pneumoperitoneum, even at normal IAP levels, leads to significant oxidativestress-induced biochemical and histologic damage to the ovaries.…”
Section: Discussionmentioning
confidence: 84%
“…An IAP over 20 mm Hg is an emergency situation, called abdominal compartment syndrome. Intraabdominal organ oxidative stress injuries occur due to changes in systemic circulation and the direct effects of IAP on abdominal vessels [13]. There is usually a physiological interval when reactive oxygen radicals and inflammatory cytokines overlay the tissue after surgical trauma, until the organism succesfully eradicates them via multiple signalling cascades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As cirurgias aórticas laparoscópicas tiveram resultados similares ou melhores do que os obtidos com a cirurgia aberta convencional quando comparados os parâme-tros hemodinâmicos, metabólicos e inflamatórios [17][18][19][20][21] e o seguimento em longo prazo 1,3,22 .…”
Section: Introductionunclassified